1998
DOI: 10.1097/00006250-199810000-00021
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Gene Mutations in Women With Papillary Serous Carcinoma of the Peritoneum

Abstract: Objective: To compare BRCA1 mutations in papillary serous carcinoma of the peritoneum and papillary serous ovarian carcinoma.Methods: Germline DNA from 17 consecutive patients with peritoneal carcinoma was screened for mutations in the BRCA1 gene using single-strand conformation polymorphism analysis. Shifted DNA bands were sequenced. Patients with germline BRCA1 mutations were screened for allelic loss in tumor DNA at the BRCA1 locus.Results: Two of the 17 patients (11%, 95% confidence interval 0.07, 0.37) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…Recent reports have concluded that the study of BRCA1 mutations would benefit molecular pathogenic research on PSPC (26,27) and that PSPC should be considered a malignancy expressed in the familial breast ovarian cancer syndrome (28). Bandera et al reported three out of 17 PSPC with germline mutations of the BRCA1 (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have concluded that the study of BRCA1 mutations would benefit molecular pathogenic research on PSPC (26,27) and that PSPC should be considered a malignancy expressed in the familial breast ovarian cancer syndrome (28). Bandera et al reported three out of 17 PSPC with germline mutations of the BRCA1 (26).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have concluded that the study of BRCA1 mutations would benefit molecular pathogenic research on PSPC (26,27) and that PSPC should be considered a malignancy expressed in the familial breast ovarian cancer syndrome (28). Bandera et al reported three out of 17 PSPC with germline mutations of the BRCA1 (26). Two cases showed 185 delAG germline mutations of the BRCA1, which is one of the three mutational hotspots in the Ashkenazi Jewish population, and the patients have a strong family history or a history of multiple breast/ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In carriers of BRCA1 and BRCA2 muta ons, cancers other than breast and ovarian tumours may develop -e.g. peritoneal cancer [508]; pancrea c cancer [509]; prostate cancer in males [510,511] and glioblastoma [512]. The la er is not that surprising, as BRCA-1 is expressed by neural stem cells [513].…”
Section: Xeroderma Pigmentosummentioning
confidence: 99%
“…The high frequency of Ashkenazi founder mutations of BRCA1 and BRCA2 in women with fallopian tube and peritoneal carcinomas was confirmed in a recent New York study which reported that 5 of 29 patients (17%) with fallopian tube cancer and 9 of 22 patients (41%) with primary peritoneal carcinoma carried one or more of these mutations [13]. Of 17 consecutive patients with papillary serous carcinoma of the peritoneum in Boston, tested for BRCA1 mutations by Bandera et al, 2, both with personal or family histories of breast and/or ovarian cancer, were found to carry the 185delAG mutation; a third patient with no personal or family history of breast or ovarian cancer carried a novel BRCA1 mutation [154]. In a screening study at the Gilda Radner Ovarian Cancer Detection Program in southern California, Karlan et al tested for BRCA1 mutations in three Jewish women of Russian-Polish ancestry with peritoneal carcinoma, and all three women carried germ-line 185delAG mutations [116].…”
Section: Genetic Susceptibilitymentioning
confidence: 99%